2022
DOI: 10.3390/ijerph19106082
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Water Quality Characteristics of the Baoan Lake Basin in China under Different Land Use and Landscape Pattern Distributions

Abstract: Land use and landscape pattern highly affect water quality. Their relationship can assist in land-use management and improve land-use efficiency. In this study, a water quality survey of rivers and lakes was performed in 2020 to analyze the effects of land use and the landscape pattern on the water quality of the rivers and lakes in the Baoan Lake basin and is expected to provide a reference for land use planning. The results demonstrated that the effects of land use on water quality were generally higher duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Therefore, clear interpretations of the relationship between landscape pattern and water quality are essential to explore effective methods for lake water quality improvement. Most of the previous studies focused on the relationship between landscape pattern and water quality of lakes in the watershed scale (Peng & Li, 2021; Ren et al., 2022). In enclosure aquaculture dominated lakes, the lake surface was usually separated into fragmented water bodies by means of nets and fences to carry out aquaculture activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, clear interpretations of the relationship between landscape pattern and water quality are essential to explore effective methods for lake water quality improvement. Most of the previous studies focused on the relationship between landscape pattern and water quality of lakes in the watershed scale (Peng & Li, 2021; Ren et al., 2022). In enclosure aquaculture dominated lakes, the lake surface was usually separated into fragmented water bodies by means of nets and fences to carry out aquaculture activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to obtain the long‐term data of these influencing factors in enclosure aquaculture lakes. It is reported that lake water quality is closely correlated with the landscape pattern in the watershed scale (Liu et al., 2012; Ren et al., 2022), which nevertheless is insignificant in the enclosure aquaculture dominated lakes due to intensive anthropogenic interferences within the lakes (He et al., 2021). Recently, Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation